Innovations as a Basis of Optimization of Educational Process in Educational Institutions of the Ministry of Internal Affairs of Russia - J. V. Strigunenko (Vestnik MGIMO-Universiteta)
In the article innovative aspects of development of system of vocational training of shots and optimization of educational process in educational institutions of the Ministry of Internal Affairs of Russia are considered. The author notes that nowadays the importance of successful modernization of the higher vocational school in innovative development of Russia is realized as a priority problem of the state and society.